Modeling potential benefits of fragmented marsh terrace restoration in Terrebonne bay, Louisiana: sediment processes interacting with vegetation and potential submerged aquatic vegetation habitat - Jung, Hoonshin; Moss, Leland; Carruthers, Tim J. B.; Di Leonardo, Diana R.; DeMarco, Kristin; Whalen, Marie; Brasher, Michael; Dijkstra, Jasper (Frontiers in Environmental Science, 2024)
Marsh terraces, constructed as a restoration and protection strategy, consist of a series of earthen berms in open water areas of the coastal wetland landscape and are being implemented across the Louisiana coast. To assess the efficacy of the marsh terraces as a nature-based solution, a small-scale, high-resolution hydrodynamic model was developed based on field sampling of vegetation and physical parameters (water level, waves, sediment, turbidity, and terrace elevation). This study tested common marsh terrace designs (e.g., chevron, linear, box, T-shape, etc.), ultimately selecting a preferred design based on the evaluation of factors such as vegetation, water depth, and sediment type on terrace stability and sediment retention under calm and storm conditions. The model results revealed that the 100 m box and the chevron designs exhibited greatest terrace stability and sediment trapping, particularly when installed perpendicular to prevailing wind and waves. The preferred terrace design was the box design due to its higher modeled resilience to wind and waves from multiple directions. Vegetation presence enhanced terrace resistance to erosion, with variations depending on vegetation type. Higher vegetation biomass, especially during the summer, contributed to the greatest stability of terraces. Greater water depth between terraces led to increased sediment retention, and terraces predominantly composed of organic-rich mud demonstrated greater stability than those with higher proportions of sand. Overall, vegetation had the greatest impact on sediment retention in the terrace field compared to water depth and sediment type. However, the potential habitat for submerged aquatic vegetation (SAV) was more influenced by water depth (i.e., 0.1 m < depth <1 m) than shear stress (<0.5 Pa). Even under storm conditions, shear stress rarely determined potential habitat for SAV, as shear stress remained relatively low within the terrace field. Potential SAV habitat was most abundant in shallow areas and increased where sediment stability was lowest (i.e., no vegetation and sand), primarily due to eroded sediment increasing the shallow area. While this model was developed using field data specific to Louisiana marshes, it can be adapted as a tool for terrace restoration project design and planning in most coastal wetlands.